3D Printing: 3D‐Printed Artificial Microfish (Adv. Mater. 30/2015). (August 2015) - Zhu, Wei; Li, Jinxing; Leong, Yew J.; Rozen, Isaac; Qu, Xin; Dong, Renfeng; Wu, Zhiguang; Gao, Wei; Chung, Peter H.; Wang, Joseph; Chen, Shaochen
<x xml:space="preserve">Abstract</x> J. Wang, S. Chen, and co‐workers use a newly developed 3D printing technique on page 4411 to print freely swimming microfish with diverse designs. The system uses light to print biocompatible hydrogels and functional nanoparticles into the biomimetic shape of fish at a feature size of 1 μm. These microfish are powered by harvesting the energy from the surrounding fluid environment and guided remotely by a magnetic field. Efficient detoxification is shown by incorporation of toxin‐absorbing functional nanoparticles. This work can be readily extended to engineer advanced functional biorobotics for diverse applications ranging from drug delivery to environmental detoxification.